2013
DOI: 10.1038/nrneph.2013.232
|View full text |Cite
|
Sign up to set email alerts
|

Fluid management for the prevention and attenuation of acute kidney injury

Abstract: In patients with acute kidney injury (AKI), optimization of systemic haemodynamics is central to the clinical management. However, considerable debate exists regarding the efficacy, nature, extent and duration of fluid resuscitation, particularly when the patient has undergone major surgery or is in septic shock. Crucially, volume resuscitation might be required to maintain or restore cardiac output. However, resultant fluid accumulation and tissue oedema can substantially contribute to ongoing organ dysfuncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
171
1
12

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(186 citation statements)
references
References 128 publications
2
171
1
12
Order By: Relevance
“…An increase of cumulative fluid balance by .1 L/d after AKI had developed was associated with an odds ratio of AKI III of 6.09 and a 95% confidence interval of 2.39 to 15.52. Previous studies have shown similar associations between fluid accumulation and harm (38)(39)(40)(41)(42), and, almost 10 years ago, an RCT in patients with acute lung injury confirmed that a conservative strategy of fluid management improved lung function without causing severe AKI (43). Importantly, we did not determine whether fluid accumulation was attributable to fluid administration or reduced urine production.…”
Section: Discussionmentioning
confidence: 71%
“…An increase of cumulative fluid balance by .1 L/d after AKI had developed was associated with an odds ratio of AKI III of 6.09 and a 95% confidence interval of 2.39 to 15.52. Previous studies have shown similar associations between fluid accumulation and harm (38)(39)(40)(41)(42), and, almost 10 years ago, an RCT in patients with acute lung injury confirmed that a conservative strategy of fluid management improved lung function without causing severe AKI (43). Importantly, we did not determine whether fluid accumulation was attributable to fluid administration or reduced urine production.…”
Section: Discussionmentioning
confidence: 71%
“…This proviso on the response to fluid resuscitation may be associated with the fluid overload conditions in AKI. 12,[38][39][40] Fluid resuscitation in participants with scores of 3 or 4 may induce positively balanced fluid retention because of strongly exaggerated output. Indeed, better responses to intravenous fluid resuscitation were observed at 6 hours than at 24 hours after LPS injection.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Although basic research has identified several pathways involved in the mechanism of AKI, including inflammation 6,7 and alterations in microcirculation, 8,9 thus enabling the development of new therapeutic strategies, specific treatments that can improve AKI outcome are not yet clinically available. [10][11][12] Notably, only modest histologic changes in the kidney gave been observed in patients with sepsis and in animal models of sepsis, 13,14 whereas septic AKI has a high mortality rate. These results strongly underscore the need for further investigations of AKI by physiologic rather than by pathologic approaches.…”
mentioning
confidence: 99%
“…39 The underlying mechanism seems to be a consecutive reduction in renal blood flow and glomerular filtration rate by a high venous pressure. 39,40 Of note, there is no good correlation between CVP and fluid responsiveness [41][42][43] and therefore other preload variables should be used. 44 Since fluid overload leads to increased morbidity in acute respiratory distress syndrome, 45 pancreatitis 46 and sepsis, 47 the authors recommend a conservative fluid regime with fluids being administered preferably after assessing responsiveness.…”
Section: Start Fluid Weaningmentioning
confidence: 99%